Miniclopedia Intiative for Agritourism Development in Rural Bali - Jayantini, I Gusti Agung Sri Rwa; Martiningsih, Ni Gusti Agung Gde Eka; Wiratama, I Gusti Ngurah Made; Karta, Ni Luh Putu Agustini (Jurnal Karya Abdi Masyarakat, 2025)
Agritourism promotes sustainable rural development by integrating agricultural activities with tourism. This community service program was designed to enhance agritourism management in Batungsel village, a village in Pupuan subdistrict, Tabanan regency, Bali through the creation of a mini-encyclopedia—referred to as the miniclopedia—which provides comprehensive information on various plants cultivated within the agritourism area. The program was implemented through a combination of four key activities: socialization, discussion, mentoring, and training. The miniclopedia serves as an educational tool for visitors, offering detailed insights into plant species, their benefits, cultivation techniques, and ecological roles. The outcomes of the program were twofold: first, the development of a comprehensive miniclopedia through collaborative efforts with local farmers and youth groups; second, the empowerment of these community members to guide visitors effectively, thereby strengthening their agricultural identity and awareness. These results were achieved through the active participation of local farmers and youth group members. This initiative is expected to enhance visitor experiences, increase environmental awareness, and contribute to the long-term sustainability of agritourism activities. Furthermore, the program exemplifies the integration of education and tourism to foster a deeper appreciation of local biodiversity and agricultural practices